Past, present, and future: comprehensive guide to anterior hip arthroplasty - Yang, Charlie C. (Annals of Joint, 2018)
The total hip arthroplasty has been lauded as one of the most successful surgeries of the 20th century. In 1962, Sir John Charnley, unveiled the Charnley hip replacement which became practical reality and the standard of hip replacement.